Factors affecting sunscreen use and sun avoidance in a U.S. national sample of organ transplant recipients. (30th January 2013) - Mihalis, E.L.; Wysong, A.; Boscardin, W.J.; Tang, J.Y.; Chren, M.M.; Arron, S.T.
Summary Background Organ transplant recipients have an increased risk of nonmelanoma skin cancers due to immunosuppressive therapy following transplantation. Use of sunscreen has been shown to reduce this risk. Objectives To identify patient and healthcare factors associated with sun‐protective behaviours in organ transplant recipients after transplantation with the goal of increasing overall sunscreen use. Methods This study utilized a cross‐sectional, retrospective survey from a national sample of 198 organ transplant recipients in the U.S.A. from 2004 to 2008 with no prior diagnosis of skin cancer. The main outcome measures were sunscreen use and sun avoidance before and after transplantation. Frequency of sunscreen use and sun exposure was obtained by self‐report on Likert scales ranging from never to always, and these responses were converted to a numerical scale from 0 to 4. Results Overall sunscreen use increased after transplantation (from a score of 1·4 to 2·1, P < 0·001). Sex, Fitzpatrick skin type, receiving advice to avoid sun from a healthcare provider, and pretransplantation sunscreen use were significantly associated with frequency of post‐transplantation sunscreen use in multivariate models. Pretransplantation sun exposure, advice to avoid sun and pretransplantation sunscreen use were significantly associated with sun avoidance post‐transplantation. Conclusions Both patient features and clinician advice are associated with sun‐protective behaviours after organ transplantation. These results will help physicians target expanded sun‐protection counselling to those patients most in need of such intervention.